PEMANFAATAN BERBAGAI JENIS FUNGI UNTUK MENINGKATKAN PERTUMBUHAN Rhizophora apiculataDI DESA NELAYAN INDAH KECAMATAN MEDAN LABUHAN - Rachel Nababan; Yunasfi Yunasfi; Mohammad Basyuni (Program studi Kehutanan USU, 2015)
Mangrove rehabilitation is one of effort to save mangrove forest. Utilization of fungi as decomposer support to increase the plantation growth for rehabilitation. Fungi as microorganism may reduct material organic. The research gives information about the fungi species in which to increase the growth of R. apiculata seedlings and can be used in rehabilitation of mangrove forest. The study was conducted from September 2014 to January 2015 using a completely randomized design (CRD) with treatment application types of fungi and five replications. There are three types of fungi namely A. flavus, A.terreus, T. harzianum, and control. Utilization of T. harzianum treatment gave the best results of R. apiculata seedlings, with an average height of 17.00 cm, diameter of 0.69 cm, leaf area of 743.36 cm2, total dry weight of 29.64 g. Compared to the control with average height of 7.36 cm, 0.54 cm of diameter, leaf area of 653.31 cm2, and 27.37 g of total dry weight.Keywords: rehabilitation, fungi, Rhizophoraapiculata, mangrove